The Peranakan Phoenix: on how the phoenix became an emblem of the Peranakan Chinese in Singapore from the 1980s–2020s - Toh, Ying Li (Nanyang Technological University, 2023)
The phoenix is a popular motif found in Peranakan Chinese artefacts. While it has been used for centuries as an auspicious symbol in Chinese culture, its role as an emblem of the Peranakan Chinese is a relatively recent phenomenon. Particularly in Singapore, it has been extensively used by Peranakan Chinese associations, museums, historians and advertisers to construct an ethnic identity in a modernised Singapore. This study examines historical, cultural and social factors that led to the ascendancy of the phoenix as an emblem for the Peranakan Chinese. There is a general consensus from prominent Peranakan Chinese scholars (such as Hwei-Fe’n Cheah in Phoenix Rising, 2010) that the phoenix has become an emblem of Peranakan Chinese identity, but scant research has been conducted on why this happened and how different players, cultural factors and historical events triggered this phenomenon. To respond to this research gap, my thesis focuses on exploring the process from the 1980s-2020s that led to the phoenix becoming an emblem of Singapore’s Peranakan Chinese. My research will conduct a visual analysis of the different phoenix representations in branding materials and logo designs, and a textual analysis of related books, press releases and articles to examine the relationships and gender roles in Peranakan Chinese culture that led to the selection of the phoenix. Interviews with members of Peranakan associations, authors and organisations involved in the logo and branding decisions will also be conducted to supplement the investigation. The importance of this research is threefold. First, it provides deeper understanding of a recent, emerging trend in Peranakan Chinese culture that has not yet been analysed in greater depth. Secondly, the research heightens the understanding of how emblems are chosen and the power held by museums, academics, associations and organisations in shaping narratives and perceptions of a certain culture. Finally, it promotes an appreciation of Peranakan Chinese culture which is still in need of preservation to ensure its continuation and survival in the modern world.